TIME SERIES MODELING OF STOCK RETURN USING EXPONENTIAL GARCH (EGARCH) MODEL - Febri Saputra, Dion
The EGARCH model is one of the asymmetric GARCH models. This model is capable of capturing residuals smaller than zero (bad news) and larger than zero (good news) in volatility. The EGARCH model has asymmetric coefficients to address the leverage effect by modeling leverage with heteroscedasticity and asymmetric effects. The modeling is based on daily stock price data of PT. Astra International Tbk. (ASII) from January 4, 2021, to October 31, 2022. ASII stock traded on the stock exchange has fluctuating values and non-constant volatility of stock returns (heteroskedastic). One risk measurement that can be used to predict stock investment risk is Value-at-Risk (VaR). The research results indicate that the best model is ARIMA(1,0,0)-EGARCH(4,5) with an AIC of -5.1082, BIC of -4.9524, and MSE of 0.0003546861. Therefore, the predicted results using the ARIMA(1,0,0)-EGARCH(4,5) model for the period of November 1, 2022, November 2, 2022, November 3, 2022, November 4, 2022, and November 7, 2022 are - 0.0019294, 0.0007587, 0.0003357, 0.0004022, and 0.0003918 respectively, with VaR values of 0.0323619, 0.03334215, 0.03086995, 0.0329255, and 0.03222855 at a 95% confidence level.